Automated auditory response detection: Improvement of the statistical test strategy. (December 2013) - Stürzebecher, Ekkehard; Cebulla, Mario
Abstract Objective: Automated auditory response detection is always performed by applying an appropriate statistical test to a sample of stimulus-related epochs of the raw EEG. The often-used sequential test strategy saves time, but the multiple testing increases the probability of falsely detected responses. Therefore, the critical test value must guarantee the specified error probability for the maximum test step number. However, response detection at all lower test step numbers is disadvantaged. We propose calculating the critical test values for each test step number, which correspond exactly to the given error probability. Design: The critical test values for each test step were calculated by the method described by Stürzebecher et al (2005). A table with the test values was implemented with customized software of the Eclipse ASSR system® (Interacoustics, Denmark). Study sample: Table-related testing was performed on a sample of raw EEG data collected during the routine clinical measurement of frequency-specific auditory steady-state responses (ASSR) for hearing threshold assessment. Results: The new test strategy leads to a significantly increased detection rate and a significantly shorter detection time. Conclusions: The new test strategy can improve the performance of the objective hearing threshold assessment and of the newborn hearing screening.